Transfer from paediatric to adult care for young adults with Type 2 diabetes: the SEARCH for Diabetes in Youth Study. Issue 4 (14th March 2018) - Agarwal, S.; Raymond, J. K.; Isom, S.; Lawrence, J. M.; Klingensmith, G.; Pihoker, C.; Corathers, S.; Saydah, S.; D'Agostino, R. B.; Dabelea, D.
Abstract: Aim: To describe factors associated with transfer from paediatric to adult care and poor glycaemic control among young adults with Type 2 diabetes, using the SEARCH for Diabetes in Youth study. Methods: Young adults with Type 2 diabetes were included if they had a baseline SEARCH visit while in paediatric care at < 18 years and ≥ 1 follow‐up SEARCH visit thereafter at 18–25 years. At each visit, HbA1c, BMI, self‐reported demographic and healthcare provider data were collected. Associations of demographic factors with transfer of care and poor glycaemic control (HbA1c ≥ 75 mmol/mol; 9.0%) were explored with multivariable logistic regression. Results: 182 young adults with Type 2 diabetes (36% male, 75% minority, 87% with obesity) were included. Most ( n = 102, 56%) reported transfer to adult care at follow‐up; a substantial proportion ( n = 28, 15%) reported no care and 29% did not transfer. Duration of diabetes [odds ratio (OR) 1.4, 95% confidence interval (95% CI) 1.1, 1.8] and age at diagnosis (OR 1.8, 95% CI 1.4, 2.4) predicted leaving paediatric care. Transfer to adult or no care was associated with a higher likelihood of poor glycaemic control at follow‐up (adult: OR 4.5, 95% CI 1.8, 11.2; none: OR 4.6, 95% CI 1.4, 14.6), independent of sex, age, race/ethnicity or baseline HbA1c level. Conclusions: Young adults with Type 2 diabetes exhibit worsening glycaemic control and loss to follow‐up during the transfer from paediatric to adult care. Our study highlights the need for development of tailored clinical programmes and healthcare system policies to support the growing population of young adults with youth‐onset Type 2 diabetes. What's new?: This is the first report of paediatric to adult healthcare transfer trends in young adults with youth‐onset Type 2 diabetes. This work studies a population‐based group of young adults with Type 2 diabetes across a wide geographic and demographic range, who are difficult to capture in research. Findings reveal substantial worsening of glycaemic control and loss to follow‐up during healthcare transfer, highlighting a previously unidentified issue for this vulnerable population. This research has implications for clinicians and healthcare systems, to focus on tailored approaches and policies for young adults with Type 2 diabetes in transition.